Diarrhoeal disease surveillance in Papua New Guinea: findings and challenges - Abdad, Mohammad Yazid; Soli, Kevin W; Pham, Bang; Bande, Grace; Maure, Tobias; Jonduo, Marinjo; Kisa, Debbie; Rai, Glennis; Phuanukoonnon, Suparat; Siba, Peter M; Horwood, Paul F; Greenhill, Andrew (Western Pacific Surveillance and Response, 2020)
Diarrhoeal diseases are among the leading causes of morbidity and mortality in the Western Pacific Region. However, data on the major causes of infectious diarrhoea are limited in many countries within the Region, including Papua New Guinea. In 2013–2014, we conducted surveillance for acute diarrhoeal illness in four provinces in Papua New Guinea. One rural health clinic from each province participated in the surveillance activity. Samples were sent to central laboratories and batch analysed for bacterial and viral gastrointestinal pathogens that are commonly associated with diarrhoea. Across the four sites, the most commonly detected pathogens were Shigella spp., Campylobacter spp. and rotavirus. In this paper, we report the results of the surveillance activity and the challenges that we faced. The lessons learnt may be applicable to other parts of the Region with a similar socioeconomic status.